Kedudukan Ayah Biologis Sebagai Wali Nikah Anak Zina Putusan MK Nomor 46/PUU-VIII/2010 (Pandangan Penghulu KUA Kecamatan Sipirok) - Mustafid, Mustafid; Anisa, Darania (Syekh Ali Hasan Ahmad Addary State Islamic University, 2024)
This research discusses the position of biological fathers in the Constitutional Court decision Number 46/PUU-VIII/2010, then will also look at the views of the Penghulu in the KUA of Sipirok District. This is field research at the location of the Sipirok District KUA, and the primary data is the decision of the Constitutional Court Number 46/PUU-VIII/2010 and the understanding of the head of the Sipirok District KUA, and secondary data in the form of books, journal articles, and other parts. Next, the data was obtained using interview and documentation techniques and then analyzed using descriptive analysis techniques. The results of this research are as follows: First, in the decision of the Constitutional Court Number 46/PUU-VIII/2010, there was a reduction in the provisions in Article 100 KHI and Article 43 of Law No. 1 of 1974 concerning marriage. This change states that children born out of wedlock have a family relationship with their mother and their mother's family and with a man recognized as their father based on scientific and technological evidence or other legally valid evidence. The child was also recognized as having a civil relationship with his father's family. So, with this decision, the biological father can become the guardian of the marriage with DNA test evidence. Second: The Penghulu references Sipirok District KUA, Constitutional Court decision Number 46/PUU-VIII/2010. It has yet to be implemented directly, and they prefer to use guardian judges according to the rules of fiqh and customs in the area.